Continuous Generation of Ethyl Cellulose Drug Delivery Nanocarriers from Microbubbles - GÜNDÜZ, OĞUZHAN (SPRINGER/PLENUM PUBLISHERS, 2013)
To investigate a new microfluidic method for the continuous preparation of hollow-shell nanoparticles of a hydrophobic polymer and the simultaneous encapsulation within these of a hydrophilic active pharmaceutical ingredient. A specially designed and constructed microfluidic device which facilitates at a junction the impingement of two liquids flowing in capillaries kept 60A degrees apart, one containing the polymer ethyl cellulose (EC) and the other active pharmaceutical ingredient amoxicillin, and a gas flowing in a capillary bisecting the two liquid flows, was used to continuously generate EC coated microbubbles at an outlet directly below the gas flow. The bubbles produce EC nanoparticles whilst encapsulating amoxicillin, and these were characterised by microscopy, zeta potential measurements, FTIR and UV spectroscopy and in vitro drug release and kinetic studies. The device produced similar to 5 x 10(6) microbubbles per minute from the surface of which EC nanocarriers were released spontaneously according to an evaporation-controlled mechanism. The gas pressure was very effective in controlling the size and size distribution of the nanocarriers. Nanocarriers with diameter between 10 and 800 nm were continuously produced by controlling the gas pressure between 110 and 510 kPa. Depending on their size, particles were capable of encapsulating 65-88% of amoxicillin which was released over similar to 12 h.
Keywords: bubbles; drug delivery; microfluidic; nanocarriers; ETHYLCELLULOSE MICROPARTICLES; RELEASE; AMOXICILLIN; MECHANISM